Integrasi Ajaran Tamansiswa dengan Ayat Ayat Pendidikan dalam Al-Quran - Ahmad Syauqi Hidayatullah; Bherrio Dwi Saputra (LP2M Universitas Sarjanawiyata Tamansiswa, 2022)
Education is the basis for the formation of character and personality of every human being as well as a form of independence for his body and soul. One of the educational figures who has been instrumental until now is Kihajar Dewantara with his Tamansiswa teachings in bringing the Indonesian people to outer and inner independence, freedom from ignorance, and oppression. However, the longer the Tamansiswa teachings are getting left behind, they are even referred to as educational teachings that are not in accordance with Islamic teachings. This problem is important to be studied more deeply, for the purpose of this research is to integrate the values of Tamansiswa teachings with educational verses in the Holy Qur’an so that it can bring up an understanding of the concept of religious-nationalist education. The type of research in this paper includes qualitative research with content analysis methods in the form of the values of Tamansiswa teachings and educational verses in the Koran with a maudhu'I interpretation approach. From the research, it was found that there is strong integration between the values of Tamansiswa teachings and educational verses in the Holy Qur’an